SISTEM MANAJEMEN KUALITAS AIR PADA LARVA UDANG VANNAMEI (LITOPENAEUS VANNAMEI) PT. ESA PUTLII PRAKARSA UTAMA (BENUR KITA) KABUPATEN BARRU PROVINSI SULAWESI SELATAN - Quraisyin, Muh. Iqbal; Tasman, Muhammad Arief Maulana (Jurnal Abdi Insani, 2024)
Litopenaeus vannamei commonly known as Vannamei shrimp or white leg shrimp, is a species of shrimp that originates from the waters of Central and South America, including Ecuador, Venezuela, Panama, and Brazil. It was introduced for cultivation in Indonesia in 2001, replacing the Litopanaeus monodon species, which experienced a decline in production due to poor water quality management and susceptibility to disease. The purpose of this internship service is to investigate water quality management techniques for vannamei shrimp larvae cultivation at PT Esaputlii. The methodology used is qualitative research with a descriptive approach. The obtained results demonstrate that the water quality management system is suitable for cultivating vannamei shrimp larvae (Litopenaeus vannamei) with oxygen levels of 31Â°, pH 7.3, salinity of 31 ppt, and alkalinity of 160 ppm. This indicates that the water quality management system can be applied to small-scale aquaculture businesses, such as companies, for the cultivation of vannamei shrimp larvae (Litopenaeus vannamei).